Communicating Agricultural Biotechnology Among Farmers In Ebonyi State, Nigeria (British Journal of Multidisciplinary and Advanced Studies, 2026)
This study was carried out to investigate the impact of communicating agricultural biotechnology to farmers in Ebonyi state. This study was anchored on Diffusion of Innovation Theory.  In conducting this research, descriptive research design was adopted. The population of the study was 2,880,383 from which a sample size of 400 was determined using Taro Yamane’s formula. Multistage sampling technique was adopted to select samples while questionnaire served as instrument of data collection. Data collected were analyzed using SPPS frequency tables, percentages and arithmetic mean in a four-point likert scale. Findings showed that majority of the respondents were fairly exposed to agricultural biotechnology information through various sources of information outlets such as the mass media. It was also found that most of the respondents agreed that kind of information contents on agricultural biotechnology was on new crops and animal species while majority of them had poor cum negative attitude towards adoption of agricultural biotechnology products and practices. The study recommended that regular communication with farmers in Ebonyi State on the nature and application of agricultural biotechnology through various mass and social media outlets and platforms, communicating Ebonyi farmers on simple and affordable or applicable agricultural biotechnology devices, innovations and products by Agricultural Development Agencies and  mass media campaigns on agricultural biotechnology should be designed with local language, contents and settings on acceptance and application of agricultural biotechnology by the farmers in Ebonyi State, Nigeria.